As contradições da expansão universitária e o movimento estudantil (2007-2012) - Vilalta, Gisele Maria da Costa (2022)
This research analyses the student movement fights between the years of 2007 and 2012, considering the contradictions fomented essentially by the Support of Restructuring Plans and Expansion of Federal Universities Program (REUNI). These events were understood and interpreted considering that, in this context, the federal institutions of university education went through an important process of expansion and enlargement of vacancies’ number, subsidized by Student’s Assistance National Program (PNAES) and by Quotas Law (Law nº 12.1711/2012), which resulted in a university students’ class reconfiguration. For that, we made a case study of the student movement performance from Philosophy, Arts and Human Sciences School (EFLCH) from Federal University of São Paulo (UNIFESP), localized in Guarulhos, São Paulo. We hypothesized that the performance agenda of the student movement from UNIFESP was determined by university expansions approved by REUNI in campuses localized outside headquarter, grouping different interests. The research was developed by performing the following procedures: a) quantitative analysis of university expansion policies through data from Education Ministry (MEC) and other sources; b) quantitative analysis of the impacts about the student’s profile using data provided by National Forum of Provosts for Student’s and Communities’ Subjects (FONAPRACE) and data about EFLCH student’s profile published by Provost for Student’s Subjects (PRAE), in partnership with Provost for Undergraduation (PROGRAD), through the Commission for Socioeconomic Profile Studies (CEPES); c) analyses of public documentary sources, such as student movement blogs, minutes of university institutional meetings and articles by newspapers with national relevance; d) interviews with ex-students engaged in the student movement during the period of time described above. The results obtained by this research demonstrated that the central hypothesis was confirmed, therefore being the university precariousness, developed into the expansion context, the main reason that brought different interests together in the student movement, although marked by shocks and arguments around this claim.